2006
DOI: 10.4049/jimmunol.177.7.4350
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke-Induced Pulmonary Inflammation and Emphysema Are Attenuated in CCR6-Deficient Mice

Abstract: Chronic obstructive pulmonary disease (COPD) is mainly caused by cigarette smoking, and is characterized by an increase in inflammatory cells in the airways and pulmonary tissue. The chemokine receptor CCR6 and its ligand MIP-3α/CCL20 may be involved in the recruitment of these inflammatory cells. To investigate the role of CCR6 in the pathogenesis of COPD, we analyzed the inflammatory responses of CCR6 knockout (KO) and wild-type mice upon cigarette smoke (CS) exposure. Both subacute and chronic exposure to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
197
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 60 publications
18
197
1
11
Order By: Relevance
“…It is also noteworthy that Th17 cells in the airways of emphysematous mice express the chemokine receptor CCR6 (40). CCR6 deficient mice have previously been found to be protected from cigarette smoke induced pulmonary inflammation and airspace enlargement perhaps indicating an important role for Th17 cells (29).…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy that Th17 cells in the airways of emphysematous mice express the chemokine receptor CCR6 (40). CCR6 deficient mice have previously been found to be protected from cigarette smoke induced pulmonary inflammation and airspace enlargement perhaps indicating an important role for Th17 cells (29).…”
Section: T Cellsmentioning
confidence: 99%
“…Such discrepencies likely reflect differences in terms of markers used to detect DC subsets as well as analysis of DC subsets from either whole lung tissue, bronchoalveolar lavage or immunohistochemistry on specific tissue sections such as the small airways. The observation that deficiency in the chemokine receptor CCR6 Volume 6 Number 2 April 2009 confers protection in a murine model of cigarette smoke induced pulmonary inflammation and emphysema points to a mechanistic role for DC in promoting disease progression (29). CCR6 is a chemokine receptor whose expression is largely associated with tissue infiltrating proinflammatory DC (as well as with specific T cell subsets) and it has subsequently been demonstrated that COPD patients have significantly elevated levels of the CCR6 ligand, CCL20, in the lung (28).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Quantification of Lm was done by light microscopy by two blinded investigators according to previously described methods [7,8] . Briefly, the Lm was measured by placing a 100×100-µm grid on each field.…”
Section: Histological Analysis Of Lung Tissuementioning
confidence: 99%
“…An antagonist of CXCR2 has been shown to abrogate lung neutrophilic inflammation in rodent models of CS exposure [11] . Lung tissue inflammation and emphysema induced by CS were significantly decreased in both CCR5-/-and CCR6-/-mice through the decreased release of macrophage inflammatory Chemokine receptor CXCR3 is important for lung tissue damage and airway remodeling induced by short-term exposure to cigarette smoking in mice www.chinaphar.com Nie L et al Acta Pharmacologica Sinica npg proteins: (MIP)-1α, MIP-1β, CXCL10, and MIP-3α [7,8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation